Petrarca a hét főbűnről: De remediis utriusque fortune, II 104-110 - Ertl, Péter; Lengyel, Réka (Antikvitás & Reneszánsz, 2019)
Petrarch’s De remediis utriusque fortune, a monumental allegorical dialogue between human passions and Reason, was one of the author’s most influential Latin works since its publication in the second half of the 1360s until the 18–19th centuries. Its popularity is proved by a very large number of manuscripts, printed editions (from the editio princeps of Strasbourg, 1468), and translations into the vernacular. Nevertheless, a modern critical text of the dialogue has not been produced yet: the bilingual French edition by Cristophe Carraud and the Italian one by Ugo Dotti, now commonly used, are based (almost) exclusively on early prints. The aim of this contribution is to offer a new edition of chapters 104–110 of the second book of the dialogue about the seven deadly sins, amending the text provided by Carraud, with the help of a few manuscripts considered authoritative by previous scholarship (Venice, Marc., Lat. Z 475; Paris, BnF, Lat. 6496; Florence, BML, San Marco 340). We are aware, at the same time, of not having established a critical edition. The Latin text is accompanied by its first modern Hungarian translation and by a detailed commentary.